An evaluation of the regenerative claims of Web3’s ReFi movement - Bennett, Kate (Frontiers in Blockchain, 2025)
The Regenerative Finance (ReFi) movement is gaining traction in the Web3 space, with numerous blockchain-based initiatives claiming alignment with regenerative outcomes. However, many of these claims remain vague or structurally unsubstantiated. This study evaluates 40 self-identified ReFi initiatives to determine the extent to which their design, governance, capital structures, and impact logic align with foundational regenerative principles. Drawing from regenerative economics, living systems theory, and regenerative organizational design, a structured evaluation framework was developed covering six dimensions across three domains: regenerative finance, real-world impact, and regenerative organizational design. The framework informed two scoring-based questionnaires, enabling systematic assessment of regenerative and impact claims. Results revealed significant variation in alignment: 50% of initiatives were categorized as Regenerative Finance (ReFi), 45% as Sustainable DeFi, and 5% as Structurally Misaligned, reflecting limited coherence between regenerative claims and actual practice. The findings showed that team diversity and initiative maturity were positively correlated with regenerative performance, and that a lack of holistic impact evaluation—across thematic dimensions and throughout operational, direct, and indirect value chains—remains a key limitation across the sector. A typology of regenerative alignment and a replicable self-evaluation tool were developed to help funders, practitioners, and protocol developers assess which ReFi initiatives are structurally aligned with regenerative principles and which remain aspirational. This research advances conceptual and practical clarity around the term “regenerative” in Web3, supporting the evolution of more accountable, transparent, and transformation-oriented financial systems in service to the Global Commons.